PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII - Devia Ananda Ditami; Utin Desy Susiaty; Iwit Prihatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop learning media based on Augmented Reality (AR) on the topic of three-dimensional geometry for grade VIII students at MTs Mujahidin Pontianak. The research method used is Research and Development (R&D) with the ADDIE model. The research subjects consisted of material experts, media experts, and grade VIII students of MTs Mujahidin Pontianak. Data collection techniques included indirect communication techniques in the form of validation sheets, teacher and student response questionnaires, and measurement techniques in the form of learning outcome tests. The results showed that the developed AR-based learning media was categorized as highly valid with a validation percentage of 94.25% from material experts and 91.28% from media experts. The practicality test results indicated a very practical category with 95% from teachers and 92.58% from students. In addition, the effectiveness test showed an effective category with a learning completeness percentage of 79.16%. Based on these results, the AR-based learning media on three-dimensional geometry is considered feasible as an alternative mathematics learning media.